A proposed model for emotional intelligence and leadership for ensuring leadership effectiveness in the Indian service sector. (30th July 2019) - ; Kumar, Pranab
The business world is highly dynamic and competitive in nature. Hence, the demand for effective leaders is also growing so that organisational outcomes can be achieved in an efficient manner. The intense work pressure demands the utilisation of a person's cognitive, emotional and physical resources, and hence, emotional intelligence (EI) is becoming increasingly important at workplace. The present study proposes a model for leadership effectiveness (LE) using structural equation modelling. Responses from 424 employees belonging to nine different industries of the Indian service sector were collected. The model reported the variance caused in the leadership effectiveness which can be attributed to emotional intelligence. The findings of the study might help in bringing some thought provoking insights for the services sector organisations. The present study utilises the trait emotional intelligence and leadership skills approach and empirically concludes that emotional intelligence affects leadership skills of the employees of the Indian service sector.